SISTEM PAKAR MENDIAGNOSA KERUSAKAN KOMPUTER DENGAN METODE FORWARD CHAINING BERBASIS WEB - Debora Margaretta Br Simanjuntak; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2022)
At present PC experts need quite a while to analyze the harm that happens to a PC, even a few professionals frequently defer their work just to deliver a